A Review on Bismuth Oxyhalide (BiOX, X=Cl, Br, I) Based Photocatalysts for Wastewater Remediation - Lv, Xincong; Lam, Frank Leung Yuk; Hu, Xijun (Frontiers in Catalysis, 2022)
Solar energy transformation over semiconductor-based photocatalysis is an ideal solution to environmental problems and future sustainability. Layered bismuth oxyhalides (BiOX, X = Cl, Br or I) are very attractive and promising photocatalysts in the environment fields. This review summarizes recent advances on the design of BiOX to enhance energy converting efficiency. Especially, the emerging techniques to enhance the photocatalytic behaviors of BiOX are discussed, including non-metal/metal doping, heterojunction engineering, carbon interfacing, coupling with noble metals, defect engineering, and morphology tuning. The application of BiOX composites in wastewater remediation is also reviewed in terms of organic photocatalytic oxidation and heavy metal ion photocatalytic reduction. Finally, the future chances and challenges of BiOX photocatalysts for practical application are summarized. In all, this review well underlies the innovative preparation of BiOX products for environment-related purposes.